Coping Strategies of Women with Breast Cancer Undergoing Chemotherapy During the COVID-19 Pandemic: A Qualitative Study - Harianto, Susilo; Nursalam, Nursalam; Maryam, Dewi; Nasir, Abd; Purwanto, Cucuk Rahmadi; Muhalla, Hafna Ilmy; Sulpat, Emuliana; Mardhika, Amellia; Soares, Domingos (Nurse Media Journal of Nursing, 2025)
Background: Chemotherapy is the primary treatment for breast cancer to prevent cancer progression, but health protocols, such as social distancing during the COVID-19 pandemic, hinder timely treatment. Although many qualitative studies have investigated the experiences of breast cancer patients during the COVID-19 pandemic, few have explored the coping strategies of women undergoing chemotherapy during this time.Purpose: This study explored the coping strategies of women with breast cancer undergoing chemotherapy during the COVID-19 pandemic.Methods: A qualitative phenomenological design was employed to explore the experiences of women living with breast cancer and their coping mechanisms. Purposive sampling was used to recruit participants who met the following criteria: (1) women diagnosed with breast cancer who had chosen to undergo chemotherapy and (2) women attending chemotherapy sessions at the treatment center. Patients with a history of severe chemotherapy side effects were excluded from the study. Data were collected through in-depth, semi-structured interviews with 25 participants, and transcripts were analyzed using thematic analysis.Results: Four key themes emerged from the data analysis, including (1) feeling the uncertainty of life, (2) emotional turbulence, (3) surviving under pressure, and (4) accepting the situation. Participants demonstrated positive adaptive coping strategies to manage the challenges of breast cancer and chemotherapy during the COVID-19 pandemic.Conclusion: Surviving and accepting conditions were identified as vital coping mechanisms that help women with breast cancer maintain their quality of life during the COVID-19 pandemic. These strategies play a crucial role in maintaining mental well-being amid uncertain and stressful circumstances.